Explanatory Phenomenal naïve realism must be non-objectivist - Machado, Ícaro Miguel Ibiapina (Griot : Revista de Filosofia, 2024)
This study focuses on a particular type of Naïve Realism known as objectivism, which suggests that the explanation of perceptual phenomenology is based on environmental things that the subject becomes acquainted with. Section 2 introduces a subtype of objectivism, “selectivism”, which aims to overcome a traditional kind of objection. However, this section highlights that the cases these objections invoke may still posit challenges (demands for explanations) to selectivism. Section 3 discusses a recent objection to objectivism and demonstrates how it can be addressed by selectivism so becomes only a challenge of this kind. However, it is important to note that, despite not providing positive refutations, these challenges are still significant. Sections 4 and 5 present the main contribution of this study, as they provide novel arguments that conclusively refute objectivism. Section 4 presents an argument that shows the falsity of objectivism as it has been presented in the literature. Nevertheless, a modified version of objectivism is proposed that could address it, although it still faces some non-definitive challenges. This reformulated theory is a novel type within the realm of Naïve Realism as a whole, as it posits that perceptions involve acquaintance with facts relative to sense organs. In contrast, Section 5 proposes an argument that positively refutes objectivism, which cannot be salvaged by any modification. Section 6 raises objections to an alternative option of Naïve Realism and, also based on the issues raised earlier in the article regarding objectivism, concludes that Naïve Realism must be subjectivist.